1999
DOI: 10.1074/jbc.274.29.20733
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p53 Function in Carcinoma Cells by the α6β4 Integrin

Abstract: The interaction of integrins with extracellular matrix is known to promote cell survival by inhibiting apoptotic signaling. In contrast, we demonstrate here that the ␣ 6 ␤ 4 integrin induces apoptosis in carcinoma cells by stimulating p53 function. Specifically, we show that expression of ␣ 6 ␤ 4 in carcinoma cells that lack this integrin stimulates an increase in the transactivating function of p53 as demonstrated by the ability of this integrin to up-regulate the expression of a p53-sensitive reporter gene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
60
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 49 publications
(57 reference statements)
7
60
0
2
Order By: Relevance
“…The e ect was transient: 18 h after plating onto ®bronectin the cells showed higher reporter gene activity, but by 36 h the activity went down. Along with recent observations showing induction of p53-mediated apoptosis in response to expression of alpha 6 beta 4 in carcinoma cells which lack this integrin (Bachelder et al, 1999) our results support the idea that activation of integrin-ERK pathways can trigger, at least in some cell contexts, p53 up-regulation. It should be noted, however, that while activation of p53 following ®bronectin plating was transient, disruption of microtubules caused sustained activation of p53 that was observed during all the period of treatment with colcemid.…”
Section: Discussionsupporting
confidence: 90%
“…The e ect was transient: 18 h after plating onto ®bronectin the cells showed higher reporter gene activity, but by 36 h the activity went down. Along with recent observations showing induction of p53-mediated apoptosis in response to expression of alpha 6 beta 4 in carcinoma cells which lack this integrin (Bachelder et al, 1999) our results support the idea that activation of integrin-ERK pathways can trigger, at least in some cell contexts, p53 up-regulation. It should be noted, however, that while activation of p53 following ®bronectin plating was transient, disruption of microtubules caused sustained activation of p53 that was observed during all the period of treatment with colcemid.…”
Section: Discussionsupporting
confidence: 90%
“…CN inhibitor-induced ␤4 phosphorylation and HD disruption may further contribute to the dissemination of the tumor by facilitating migration. Interestingly, ␤4 is known to activate p53, thus promoting apoptosis (36), and therefore, it would be valuable to determine whether phosphorylation can modify this capability and add to the effects of ATF3.…”
Section: Discussionmentioning
confidence: 99%
“…In these cells, there is some evidence for pathways linking integrin ␣6␤4 to activation of p53. Bachelder et al (21) showed that overexpression of ␣6␤4 integrin in suspended carcinoma cells, where the integrin would be unoccupied by any ECM ligand, activates p53 and induces apoptosis. They also reported that antibody crosslinking of unoccupied integrins accelerated apoptosis; however, this effect is unlikely to reflect interactions of ␣6␤4 with basement membranes, because adhesion to basement membranes promotes epithelial cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…In epithelial and endothelial cells, integrin ligation regulates cell survival such that detachment from the ECM rapidly induces apoptosis (17,18). In some of these cases, cell death results from increased levels of p53 or Bax caused by detachment or inhibition of integrins or by overexpression of unligated integrins (19)(20)(21). Correspondingly, binding of some carcinomas to the ECM protects against apoptosis initiated by DNA damage (22).…”
mentioning
confidence: 99%